Prohibition of Cross-Media Ownership as a Means of Limiting Media Concentration (on Example of R. Murdoch’s Companies “News Corp” and “XXI Century Fox” by R. Murdoch in Australia, Great Britain and the USA) - Z. K. Nadirova (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
This article is an analysis of the practice of implementation and effectiveness of laws prohibiting cross-media ownership in Australia, the UK and the USA. The author pays attention to the evolution of antitrust laws in the field of media business and modern principles of their implementation, as well as traces the connections between the liberalization of antimonopoly regulation and intensification of the process of concentration of media ownership. The research urgency is attributable to the fact that the consolidation of media ownership today has reached a critical level and poses a serious threat to freedom of expression and media diversity in most countries of the world. In the present work this problem is explored on the example of activity of the companies “News Corp” and “XXI Century Fox” owned by R. Murdoch. The author analyses the acquisition transactions of print and broadcast media (already completed by R. Murdoch and currently under consideration by competition authorities) from the point of view of their conformity to the current legislation, as well as their impact on the level of media concentration, availability of information services and their diversification. The article presents the latest data on the state of the media market in Australia, the UK and the US and recent reforms in the field of media regulation, which allows the author to draw a conclusion about the expected intensification of the process of concentration of the media ownership in the coming years and the increase in the number of its negative effects on the back of further liberalization of media regulation and inefficient work of the Antimonopoly services.